Comprehensive Physiology 2016
DOI: 10.1002/cphy.c150040
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiology of Skin Thermal Sensations

Abstract: Undoubtedly, adjusting our thermoregulatory behavior represents the most effective mechanism to maintain thermal homeostasis and ensure survival in the diverse thermal environments that we face on this planet. Remarkably, our thermal behavior is entirely dependent on the ability to detect variations in our internal (i.e. body) and external environment, via sensing changes in skin temperature and wetness. In the past 30 years, we have seen a significant expansion of our understanding of the molecular, neuroanat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 301 publications
(792 reference statements)
4
78
0
Order By: Relevance
“…In humans and primates, fast‐conducting myelinated Aδ‐fibres innervate the skin with varying density depending on the skin site (Filingeri, ), selectively respond to skin cooling (range 30–14°C; maximal impulse frequency within 27–22°C range; conduction velocity 3.8–4.4 m s −1 ; receptive field <1 mm) and mediate innocuous cold sensations (Darian‐Smith et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans and primates, fast‐conducting myelinated Aδ‐fibres innervate the skin with varying density depending on the skin site (Filingeri, ), selectively respond to skin cooling (range 30–14°C; maximal impulse frequency within 27–22°C range; conduction velocity 3.8–4.4 m s −1 ; receptive field <1 mm) and mediate innocuous cold sensations (Darian‐Smith et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…). In contrast, unmyelinated C fibres respond to skin warming, fire optimally within a temperature range of 30–45°C (maximal impulse frequency within 36–42°C range; conduction velocity 0.4–2 m s −1 receptive field <1 mm) and mediate innocuous warm sensations (Konietzny & Hensel, ; Filingeri, ; but note that a subclass of C fibre, i.e. C2, responds to noxious skin cooling <15°C and mediates noxious cold sensations; Campero et al .…”
Section: Introductionmentioning
confidence: 99%
“…In humans, magnitude estimation of skin thermal sensations is determined by afferent impulses produced by peripheral skin thermoreceptors (Filingeri et al, 2017b) and by their integration operated by central (sub-cortical/cortical) neural structures (Filingeri, 2016). Due to the central, and not peripheral, nature of MS lesions within the nervous system (Noseworthy et al, 2000), it could be therefore suggested that the pronounced reduction in cold sensitivity observed in our relapsingremitting MS group could be dependent on heat-induced alterations in the processing of afferent somatosensory inputs within central neural centers.…”
Section: Magnitude Estimation Of Warm and Cold Stimulimentioning
confidence: 99%
“…Indeed, the neuro-anatomical and -physiological differences between the human peripheral and central pathways for cold (served by myelinated nerve fibers) and warm (served by non-myelinated nerve fibers) skin thermosensitivity (Dostrovsky & Craig, 1996;Iannetti et al, 2003), allow for the independent assessment of myelinated and nonmyelinated afferent neural pathways (Filingeri, 2016). The opportunity to concurrently and non-invasively evaluate both myelinated and non-myelinated afferent pathways is particularly relevant in the context of a demyelinating disease such as MS (Noseworthy et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation